Pengembangan Media Pembelajaran Kartu Domino Untuk Materi Nilai Mutlak - Dornama Putri Lumbansiantar; Faiza Faiza; Nathasya Farah Dilla; Nurfahmi Rachman Haqiqi; Uswatun Hasanah (Journal of Instructional Development Research, 2020)
This research aims is to develop a learning media, namely dominoes as an interesting and interactive learning media, especially on absolute value material. This type of research is development research. This study uses the ADDIE development model, which consists of 5 stages, namely analysis, design, development, implementation and evaluation. The research subjects consisted of 3 students with different intellectual abilities, namely low, middle and high at grade X high school level. The results showed that there was an increase in understanding of mathematical concepts using the developed domino card media.